Methodology for testing the influence of buoyancy and hydrodynamics on swim performance with and without a wetsuit - Harnish, C. R. (Research & Investigations in Sports Medicine, 2018)
Purpose: The purpose of this pilot study was to develop test methodology that would allow for an estimation of the relative contributions of buoyancy and hydrodynamics on swim performance. Methods: One trained swimmer completed three familiarization trials followed by eighteen randomized swim sessions where each condition no wetsuit (NS), low buoyancy wetsuit (LBW), high buoyancy wetsuit (HBW), NS plus pull buoy (NSB), and HBW matched to buoy buoyancy (HBW+) were tested four times each. Buoyancy for all conditions was measured via hydrostatic weighing system. All data are presented as means+SD and change scores (95% CI). Results: Coefficients of variations with each condition were about 2%. DB decreased by 2.29% for LBW, 2.80% for HBW, 1.93% for NSB, and 1.96% for HBW+, which resulted in an increase in buoyancy lift force. LBW and HBW improved 800-yd swim times over NS -70.6 (-86.2, -55.0) sec, and -69.1 (-84.0, -54.3) sec, respectively. Swim times for 100-yd were also similar between LBW, -9.4 (-10.7, -8.1) sec, and HBW, -7.9 (-11.4, -4.5) sec. Neither stroke rate nor total strokes differed between LBW and HBW, though both appeared significantly lower than NS. In HBW+ trials, the difference in 800- yd and 100-yd times between NSB and NS was -25.2 (-60.3, 10.0) and -1.7 (-19.6, -16.3), respectively, while HBW+ vs NSB 800-yd and 100-yd time differences were -26.6 (-28.3, -24.9) and -5.7 (18.9, 7.5). Conclusion: The outlined protocol can produce reliable results. These data support earlier assertions that buoyancy may reach a point of diminishing returns, and also indicate that wetsuit hydrodynamics play larger role in swim performance as velocity increases. The protocol outlined could aid in optimal wetsuit design without the need for advanced testing equipment.